Pemanfaatan Limbah Cangkang Telur Sebagai Bahan Substitusi Semen Pada Beton - Agnes Sentani Klau; Frans Phengkarsa; Olan Jujun Sanggaria (Paulus Civil Engineering Journal, 2021)
Technological developments can have positive and negative impacts on everyday human life. The most common negative impact is the waste generated from every human activity. Most of this waste is simply dumped into nature without treatment. One of the most common waste found is eggshell waste. The amount of eggshell waste continues to increase, but it is not managed and not used optimally so that the waste needs to be processed, such as utilizing the eggshell waste in a concrete mixture. This study aims to determine the effect of using eggshell waste as a cement substitution material with variations of eggshell waste powder of 0%, 4%, 6% and 8% on the strength of the concrete. The quality of the concrete plan (f'c) in this study is 25 MPa. From the results of the study, the compressive strength of concrete was 27.351 MPa, 25.842 MPa, 23.201 MPa and 21.504 MPa, the value of the split tensile strength of concrete was 2.712 MPa, 2.499 MPa, 2.264 MPa and 2.146 MPa, the value of the modulus of elasticity. concrete were 21912,043 MPa, 17437.327 MPa, 14447,336 MPa and 12290.684 MPa, respectively. From the results of this study, it is known that concrete using eggshell waste powder as a cement substitution material with variations of 0% and 4% can meet the quality of the concrete plan.